TINJAUAN SEMIOTIKA PUISI IBU INDONESIA KARYA SUKMAWATI SOEKARNOPUTRI - Enung Nurjanah; Suci Lestari; Dida Firmansyah (IKIP Siliwangi, 2018)
The Reviews semiotics poetry Indonesia by Sukmawati Soekarnoputri is one of literature work form the expression of the human person through experiences, thoughts, feelings, ideas, passions, beliefs in a concrete form of images that evoke charm with the tools of language. The method used in this research is descriptive qualitative, Descriptive analysis method is research method used to illustrate the problems that occur in the present or in progress. To create literature work authors usually make use of semiotics in his work. One of the poems analyzed is poetry “Ibu Indonesia” who wants to convey to readers about the pride of poets on the civilization of an island region, sea called the Indonesian nation. Any literary works in the form of poetry can be said one genre of literary works that many use the mark as aesthetic builder. The researcher focused the semiotic review of poetry in terms of significance and interpretant. “Ibu Indonesia” which is seen from the significance (meaning) contained in this poem we as a young generation do not forget the struggle and culture of Indonesia.